Hydrogen storage in scandium doped small boron clusters (BnSc2, n=3–10): A density functional study - Ray, Shakti S.; Sahoo, Smruti R.; Sahu, Sridhar (International journal of hydrogen energy, 2019)
In this work, we present the hydrogen adsorption capacity of Sc doped small boron clusters (BnSc2, n = 3–10) using density functional theory. Almost no structural change was observed in the host clusters after hydrogen adsorption. Stabilities of the studied clusters were confirmed by various reactivity parameters such as hardness (η), electrophilicity (ω), and electronegativity (χ). The average adsorption energies was found in the range of 0.08–0.19 eV/H2 inferring physisorption process, and the fact is also supported by the average distance from Sc to H2 molecules which was in the range of 2.13 Å-2.60 Å. All the clusters were found to have gravimetric density satisfying the target set by the U.S. Department of Energy (US-DOE) (5.5 wt% by 2020). From Bader's topological analysis, it was confirmed that the nature of interaction was likely to be somewhat closed shell type. ADMP molecular dynamics simulations study was performed at different temperatures to understand the adsorption and dissociation of H2 from the complexes. [Display omitted]